HUBUNGAN ANTARA KETERAMPILAN PUBLIC SPEAKING DENGAN KEMAMPUAN BERPENDAPAT PADA MATERI KEANEKARAGAMAN HAYATI DI KELAS X MAN 1 SAMARINDA PLUS KETERAMPILAN DAN RISET - Wanda, Noor; Rambitan, Vandalita M Magdalena (UNIB Press, 2025)
This study investigates the relationship between students' public speaking abilities and their capacity to articulate opinions on biodiversity topics in Class X at MAN 1 Samarinda (specializing in skills and research). Employing a quantitative approach with a correlational design, the researcher selected participants using purposive sampling from classes X-A and X-C. Data were analyzed using the Spearman correlation test, which produced a p-value of 0.001 indicating statistical significance (p < 0.05). The findings reveal a strong, positive, and significant relationship between public speaking proficiency and students’ ability to express views on biodiversity.